Understanding the use of co-design methods for research involving older adults living with HIV: A scoping review protocol. - Paige Brown; Hardeep Singh; Esther Su; Luxey Sirisegaram; Sarah E P Munce; Andrew D Eaton; Alice Zhabokritsky; Stuart McKinlay; Kristina M Kokorelias (PLoS ONE)
There is a growing population of adults aged 50 years or older living with HIV, facing unique challenges in care due to age, minority status, and stigma. Co-design methodologies, aligning with patient-centered care, have potential for informing interventions addressing the complex needs of older adults with HIV. Despite challenges, co-design has shown promise in empowering older individuals to actively participate in shaping their care experiences. The scoping review outlined here aims to identify gaps in existing co-design work with this population, emphasizing the importance of inclusivity based on PROGRESS-Plus characteristics for future patient-oriented research. This scoping review protocol is informed by the Joanna Briggs Institute Manual to explore co-design methods in geriatric HIV care literature. The methodology encompasses six stages: 1) developing research questions, 2) creating a search strategy, 3) screening and selecting evidence, 4) data extraction, 5) data analysis using content analysis, and 6) consultation with key stakeholders, including community partners and individuals with lived experience. The review will involve a comprehensive literature search, including peer-reviewed databases and gray literature, to identify relevant studies conducted in the past 20 years. The inclusive criteria focus on empirical data related to co-design methods in HIV care for individuals aged 50 or older, aiming to inform future research and co-design studies in geriatric HIV care. The study will be limited by the exclusion of papers not published or translated to English. Additionally, the varied terminology used to describe co-design across different research may result in the exclusion of articles using alternative terms. The consultation with key stakeholders will be crucial for translating insights into meaningful co-design solutions for virtual HIV care, aiming to provide a comprehensive synthesis that informs evidence-based strategies and addresses disparities in geriatric HIV care.